Analisis Keterbatasan Teori Behaviorisme sebagai Pendekatan Pedagogis dalam Proses Belajar Andrew Neiman pada Film Whiplash - Firman Ade Rizqi Prasetyo (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2026)
This study examines the representation of pressure-based pedagogy in the film Whiplash through the theoretical perspectives of Operant Conditioning, power relations, and critical pedagogy. The research is grounded in the ongoing debate surrounding pressure-oriented instructional practices, which are often regarded as effective in enhancing performance while simultaneously posing substantial psychological risks to learners. The study addresses how pressure-based pedagogy is represented in the learning process and evaluates its pedagogical implications through a qualitative documentary research approach. Data were collected through systematic observation of scenes, dialogues, and character interactions portrayed in the film. The findings reveal that Fletcher effectively employed reinforcement, punishment, and behavioral shaping to improve Andrew Neiman's musical performance; however, these strategies also generated psychological distress, social isolation, and emotional exhaustion that undermined the learner's well-being. The analysis demonstrates that Whiplash offers a critical reflection on the limitations of behaviorist pedagogical practices when implemented through coercive and authoritarian approaches. The study concludes that educational success should not be measured solely by performance outcomes but should also prioritize learners' psychological well-being, autonomy, and humanistic development as essential components of meaningful education.